Science, Politics and Religion: Debates about Verbiest’s Involvement at the Astronomical Bureau (The Macau Ricci Institute Journal, 2023)
As we celebrate the 400th anniversary of Ferdinand Verbiest’s birth, it is quitemeaningful to remember the most tragic event in his own life and in the history of the Catholic mission in China, the Calendar Case instigated by Yang Guangxian which led to the nationwide prohibition of Christianity and the arrest of almost all of the missionaries.Recent studies, based on Manchu, Chinese and Western writings, have helped us to better understand how Kangxi seized the opportunity of the Calendar Case to get rid of the regents and to assume personal rule. In this short essay, we shall look at how the missionaries who were exiled in Canton evaluated the involvement of Verbiest at the Imperial Astronomical Bureau.Their discussions shed a new light on the fragility of a synthesis between science, politics and religion which overlooks their mutual boundaries.